2018
DOI: 10.4045/tidsskr.17.1027
|View full text |Cite
|
Sign up to set email alerts
|

Myokardfibrose

Abstract: Institutt for sirkulasjon og bildediagnostikk Norges teknisk-naturvitenskapelige universitet og Klinikk for hjertemedisin St. Olavs hospital Han har bidratt med idé til artikkelen, utforming/design, datainnsamling, analyse av data, tolking av data, litteratursøk, utarbeiding/revisjon av selve manuset og godkjenning av innsendte manusversjon. Torvald Espeland er stipendiat, spesialist i indremedisin og lege i spesialisering i hjertesykdommer. Forfatter har fylt ut ICMJE-skjemaet og oppgir ingen interessekonflik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 37 publications
(88 reference statements)
0
33
0
1
Order By: Relevance
“…This is supported by MRI studies in patients with pulmonary hypertension that have shown elevated T1 times in the entire LV, which is correlated with changes in the eccentricity index (Reiter et al, ). The aforementioned computational studies in our lab have suggested a potential mechanism by showing that increased RV pressure overload causes increased LV myocardial stress (Kheyfets et al, ), which is a biomechanical initiator for fibroblast activation (Espeland, Lunde, B, Gullestad, & Aakhus, ). However, these modeling studies were conducted on a human heart model and an actual estimate of myocardial stress was not available for the mice in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by MRI studies in patients with pulmonary hypertension that have shown elevated T1 times in the entire LV, which is correlated with changes in the eccentricity index (Reiter et al, ). The aforementioned computational studies in our lab have suggested a potential mechanism by showing that increased RV pressure overload causes increased LV myocardial stress (Kheyfets et al, ), which is a biomechanical initiator for fibroblast activation (Espeland, Lunde, B, Gullestad, & Aakhus, ). However, these modeling studies were conducted on a human heart model and an actual estimate of myocardial stress was not available for the mice in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while evidence of LV perivascular fibrosis may be a marker of elevated myocardial stress, there has been debate about its implication for function. Traditional thinking has suggested that myocardial fibrosis depresses electrical and mechanical function in the heart (Espeland et al., ), but some studies have suggested that fibrosis is both an adaptive and maladaptive response (Andersen et al, ). Therefore, it is unlikely that the minimal fibrosis we observed in the LV of PAB mice is somehow contributing to reduced torsion rate or EF, but is likely a benign response to biomechanical and biochemical stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Myofibroblasts have an increased production of proteins that are deposited in the extracellular matrix. This increase in collagen between myocytes leads to an increased stiffness of the myocardium [18,19], and causes structural and electrical changes that predispose patients to arrhythmias, heart failure and ischemia. Increased myocardial stiffness is therefore a second clinical indicator of fibrosis.…”
Section: Myocardial Fibrosismentioning
confidence: 99%
“…Interstitial (or diffuse) fibrosis is characterized by diffuse spread of extracellular collagen and is believed to be reversible if treated early. This type is also seen in elderly people, and in diseases such aortic stenosis and coronary heart disease without infarction [19]. Fibrosis is currently diagnosed invasively with biomarkers measured in biopsies and blood tests, and non-invasively with MRI (with and without contrast), cardiac CT and echocardiography (by identifying areas of increased reflectivity).…”
Section: Myocardial Fibrosismentioning
confidence: 99%
“…Torvald Espeland og medarbeidere har skrevet en verdifull og interessant oversikt over myokardfibrose, men utelater å nevne et viktig kardiologisk fagfelt ved myokardfibrose, nemlig medfødte hjertefeil hos både barn og voksne (1). Medfødt hjertefeil forekommer hos ca.…”
unclassified